Zeolite-Iike Metal—Organic Frameworks as Platforms for Applications: On Metalloporphyrin-Based Catalysts. - Alkordi, Mohamed H.; Yunling Lui; Larsen, Randy W.; Eubank, Jarrod F.; Eddaoudi, Mohamed (Journal of the American Chemical Society, 2008)
The article offers information on metal-organic frameworks (MOFs). It states that MOFs have emerged as a particular class of functional solid-state materials. It notes that a major impetus to advance MOF applications is the development of new pathways and strategies to construct made-to-order MOFs as platforms suitable to a desired application. The approach that was developed for the construction of MOFs based on their molecular building blocks (MBBs) is discussed.